Gut microbiota composition correlates with insomnia severity: insights from high-throughput sequencing analysis - Xu, Zhe; Zhang, Jinxia; Zhou, Haifang; Zhang, Lei; Zhang, Xiuhong (Frontiers in Microbiology, 2026)
ObjectiveThis study investigates differential alterations in gut microbiota characteristics across varying degrees of insomnia severity, aiming to provide empirical evidence elucidating the relationship between sleep disorders and the gut microbiome.MethodsA total of 120 insomnia patients, treated at the Clinical Psychology Department of Hangzhou Hospital of Traditional Chinese Medicine between October 2023 and May 2024, were enrolled and categorized into mild (Group B, n = 16), moderate (Group C, n = 42), and severe (Group D, n = 42) cohorts based on Pittsburgh Sleep Quality Index (PSQI) scores. A control group of 20 healthy volunteers (Group A) was recruited for comparison. Fecal samples were collected from all participants for gut microbiota DNA extraction. High-throughput sequencing of the 16S rDNA was performed on the Illumina NovaSeq platform to analyze the alpha diversity, beta diversity, and species composition of the gut microbiota across the groups.ResultsAlpha diversity analysis revealed significantly elevated Chao1 and ACE indices in the insomnia cohorts compared to controls (p < 0.01). Notably, the Shannon index was significantly elevated only in the mild group (Group B, p < 0.05). Beta diversity analysis indicated significant differences in the microbial community structure among groups, with a gradient shift corresponding to increasing PSQI scores. Compositional analysis revealed a progressive decline in the Firmicutes/Bacteroidetes (F/B) ratio that paralleled increasing insomnia severity. The abundance of Clostridia demonstrated a graded decline with increasing insomnia severity, with a significant reduction of approximately 15% observed even in the mild sleep disorder group. LEfSe analysis identified distinct differential microbiota for each group: the healthy group was characterized by Firmicutes and Akkermansia, while the sleep disorder groups were, respectively, enriched in Fusobacteriota, Cyanobacteria, and Desulfobacterota.ConclusionGut microbiota structure is intrinsically linked to insomnia severity, characterized by a diminished F/B ratio, reduced Clostridia abundance, and enrichment of pro-inflammatory taxa. The reduction in SCFA-producing Clostridia may impair neuro-immune regulation via the gut-brain axis, potentially exacerbating sleep dysregulation.